STRUKTUR ALTERNATIF FILM BOX OFFICE INDONESIA PASCAREFORMASI - Budiman Akbar (Jurnal Ilmiah Publipreneur, 2013)
This research aims at analyzing Indonesia box office film structure. In this case, the film is Jelangkung. The researcher uses a descriptive comparative method. The result shows Jelangkung film use an alternative structure within the pattern of three segments, using a logical clause on the cause-effect story relationship.